1948
DOI: 10.1021/ja01187a063
|View full text |Cite
|
Sign up to set email alerts
|

Cyclobutane Derivatives. IV. Ziegler Bromination1a of Methylenecyclobutane1b,2

Abstract: Ziegler Bromination of Methylenecyclobutane 2517 No secondary alcohol was detected; the larger part of the liquid began to decompose and carbonize at a bath temperature of 180°and pressure of 4 mm.An average of results from two runs gave amorphous solid, 12.5 g.; dibenzyl, 6.3 g.; tarry, carbonaceous residue, 14.5 g.Table I provides essential data. Yields in each case are averages from two runs. Summary 1. The reaction of a, /3-dichloropropionaldehyde with phenylmagnesium bromide, «-hexyl-magnesium bromide, cy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
8
0

Year Published

1952
1952
2009
2009

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…When 13 was passed through a basic ion-exchange column, a lactone zwitterion (15) was obtained, which, when treated with sodium nitrite, gave the known dilactone 16. These data demonstrated that NBS reacted with 7 without skeletal rearrangement of 7 to give an adduct (12) in which the succinimidyl group and bromine atom had become attached at C-5 and C-6. In addition, the isolation of the known lactones 14 and 16 under the conditions described showed the bromine atom to be in the exo (ß) configuration in the adduct 12. The isolation of 14 and 16 with carboxyl groups of different stereochemistry at C-3 can be explained as follows.…”
mentioning
confidence: 88%
See 3 more Smart Citations
“…When 13 was passed through a basic ion-exchange column, a lactone zwitterion (15) was obtained, which, when treated with sodium nitrite, gave the known dilactone 16. These data demonstrated that NBS reacted with 7 without skeletal rearrangement of 7 to give an adduct (12) in which the succinimidyl group and bromine atom had become attached at C-5 and C-6. In addition, the isolation of the known lactones 14 and 16 under the conditions described showed the bromine atom to be in the exo (ß) configuration in the adduct 12. The isolation of 14 and 16 with carboxyl groups of different stereochemistry at C-3 can be explained as follows.…”
mentioning
confidence: 88%
“…
N-Bromosuccinimide was found to add to the double bond of bicyclo [2.2.1] -5-heptene-e«do-ct's-2,3-dicarboxylic anhydride in the presence of benzoyl peroxide to yield the eis adduct, eio-5-bromo-ezo-6-succinimidobicyclo-[2.2.1]heptane-endo-cfs-2,3-dicarboxylic anhydride (12). In addition, N-bromosuccinimide rearranges under the conditions of the reaction to give (3-bromopropionyl isocyanate.N-Bromosuccinimide (NBS) has been used extensively as an allylic brominating agent for approximately twenty years.4 5Bloomfield68 and Hey6b first suggested that this reaction proceeded by a radical chain mechanism, and further support for this postulation was provided by Schmid and Karrer.6 More recently, Dauben and McCoy7 reported a very thorough investigation of
…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…(8) The amount of trimethylamine formed may be taken as a measure of the diolefin-producing reaction (trimethylamine formation from the vinylic quaternary base is unlikely and allylic alcohol production is apparently insignificant); by an extension of this reasoning dimethylamine measures the reaction leading to III. (9) Giving a dibromide only one of whose bromines was displaced on treatment with trimethylamine in benzene. ture has been confirmed by Applequist and Rob-erts10 through a comparison with authentic II10 of a sample of hydrocarbon11 obtained in the present research.…”
mentioning
confidence: 99%